All-sky imaging observations of mesospheric fronts from Silchar (24.7°N, 92.8°E) - Chauhan, Nilesh; Gurubaran,S.; Moulik, S.; Das, P.K.; Bagiya, Mala S. (My University, 2022)
An All-Sky Airglow Imager was operated at Silchar (24.68°N, 92.76°E), India from 9 to 11 December 2018, during a special observational campaign. We report the presence of two simultaneous mesospheric fronts observed in OH airglow emission propagating orthogonal to each other on the night of 9 December 2018, which was a rare and unique observational feature. A third mesospheric front was observed on 11 December 2018. Temperature and OH intensity measurements from SABER instrument onboard TIMED satellite were used to characterise the environment of the frontal propagation. Though one of the frontal structures resembled a mesospheric bore, the other frontal events do not satisfy a few of the requirements to be met for a bore. We also report the modulation of the OH emission layer by the passage of the mesospheric front on the night of 11 December 2018.
Keywords: Gravity waves; Mesospheric fronts; Bores; Ripples; Airglow imaging